Does preoperative intravenous tramadol or dipyrone prevent postoperative pain with patient controlled analgesia? - Önal, S. Ateş; Yaşar, M.A.; Akin, M.; Bayar, M.K.; Gök, Ü.; Erhan, Ö.L. (My University, 2003)
The aim of the present study is to test the hypothesis that preoperative intravenous tramadol or dipyrone usage with patient controlled analgesia method reduces postoperative pain and analgesic consumption. ASA I-II, 40 men scheduled for septoplasty were included in the study. Subjects were randomly allocated into one of the following groups: Prior to anesthetic induction, Group C1 (n=10) received i.v. 100 mg tramadol in 100 ml isotonic saline solution; Group C2 (n=10) recieved i.v. 100 ml saline solution without drug; Group N1 (n=10) recieved i.v. 1.0 g dipyrone in 100 ml saline solution and Group N2 (n=10) recieved i.v. 100 ml saline solution without drug. A standard general anesthesia technique was used. After recovery of all subjects from anesthesia, the pain intensity was evaluated on a 4-point categorical scale. There was no significant difference between the groups C1, C2, N1 with respect to the degree of satisfaction of the patients. Preoperative infusions of tramadol or dipyrone preempt (reduce) postoperative pain with patient controlled analgesia.
Hasta kontrollü analjezi yöntemiyle preoperatif intravenöz tramadol veya dipyrone kullanimi postoperatif a?riyi önler mi?
Keywords: Dipyrone; Postoperative patient controlled analgesia; Tramadol